Achieving transformational sustainable land Intensification: Integrated general equilibrium and portfolio analysis for Senegal - Pradesha, Angga; Siddig, Khalid; Pauw, Karl; Thurlow, James (Elsevier, 2025)
Feeding a growing global population while conserving natural resources remains a central challenge of Sustainable Intensification (SI). Despite decades of SI efforts, cropland expansion in many developing countries continues to accelerate, contributing to deforestation and biodiversity loss. Even with observed increases in crop yields, studies suggest that farmers continue to expand cropland, underscoring the need to consider market dynamics and the economywide effects of productivity gains. This study offers a new perspective on achieving transformational sustainable land intensification by treating farming activities as investment decisions shaped by risk and return under production and markets uncertainties. Unlike the traditional SI strategies that focus on efficiency gains through improved inputs or agronomic practices, we apply an optimal portfolio analysis to cropland allocation, aiming to enhance farming efficiency by considering market interconnections across sectors. Using Senegal as a case study, we demonstrate that adopting an optimal diversification strategy on new cropland investment could reduce land expansion needs by up to 68 % by 2030. This strategy not only helps mitigate emissions and reduce water footprint but also enhances crop biodiversity. Socioeconomic and environmental benefits are found to be greater when the country promotes high-value crops in its portfolio, such as fruits and vegetables, compared to grain crops. Our findings also contribute to ongoing debates around land-sparing versus land-sharing strategies and offer new insights into the drivers of cropland expansion in light of current global land use patterns.